Implementing Six Sigma and Lean a practical guide to tools and techniques - Basu, Ron (Elsevier Butterworth-Heinemann, 2009)
This is a comprehensive, user-friendly and hands-on book that is a single source of reference of tools and techniques for all quality practitioners. Implementing Six Sigma and Lean covers the basics of how to manage for consistently high quality and gives good coverage of both simple tools and advanced techniques which can be used in all businesses. This book provides guidance on how to use these tools for different situations such as new start-up companies, stalled projects and the constant achievement of high quality in well-established quality regimes. Case studies are included that encoura.
Keywords: Six sigma (Quality control standard); Total quality management.; Total quality control.; elektronické knihy; electronic books